Mild cognitive impairment in the elderly is associated with volume loss of the cholinergic basal forebrain region - Muth, Kathrin; Schönmeyer, Ralf; Matura, Silke; Haenschel, Corinna; Schröder, Johannes; Pantel, Johannes (Biological psychiatry, 2010)
Background - Cholinergic neurons within the basal forebrain are assumed to be an early (preclinical) manifestation site of pathological changes in Alzheimer's disease (AD). - Methods - We used morphometric magnetic resonance imaging (MRI) to detect and quantify atrophic changes in the basal forebrain of subjects suffering from amnestic mild cognitive impairment (aMCI). Three Tesla magnetic resonance (MR) data of 26 aMCI patients, 46 cognitively normal elderly control subjects (CO), and 12 patients suffering from Alzheimer's dementia were analyzed, including segmentation and quantification of brain tissue as well as a segmentation of basal forebrain structures (substantia innominata [SI]). - Results - We found the volume of the SI to be significantly different between groups in that control subjects showed the largest SI volumes, followed by aMCI and AD patients. - Conclusions - These results are in line with the hypothesis that cell loss within the cholinergic basal forebrain regions occurs already in the early (predementia) stage of AD. In vivo quantification of these changes might be of use as a novel neuroimaging marker of cholinergic neurodegeneration in AD.
Erstmals am 17 April 2009 online veröffentlicht
Gesehen am 17.05.2023